2005
DOI: 10.1111/j.1468-3083.2005.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver failure and transplantation after itraconazole treatment for toenail onychomycosis

Abstract: Three weeks after completing a 4-pulse course of itraconazole for toenail onychomycosis, a 25-year-old woman patient developed severe liver crisis and required an emergency liver transplant. We report the case and discuss the use of itraconazole in onychomycosis and dermatomycoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Furthermore, in paInhibition of MDR3/ABCB4 by Itraconazole tients 1 and 2, serum ITZ concentrations were significantly high, which should increase the risk of hepatotoxicity. Patients 1, 2, and 3 suffered from ITZ-induced liver injury 62, 20, and 2 days after starting ITZ-administration, respectively (Table 1), which is consistent with the previous report that the time period to exhibit elevations in LFTs after starting ITZ administration varied from several days to several weeks in ITZ-induced liver injury (Lavrijsen et al, 1992;Hann et al, 1993;Gallardo-Quesada et al, 1995;Srebrnik et al, 2005). In the present study, day 0 was defined as the day on which ITZ administration was started for patients 1 and 2.…”
Section: Abnormalities In Lftssupporting
confidence: 80%
See 3 more Smart Citations
“…Furthermore, in paInhibition of MDR3/ABCB4 by Itraconazole tients 1 and 2, serum ITZ concentrations were significantly high, which should increase the risk of hepatotoxicity. Patients 1, 2, and 3 suffered from ITZ-induced liver injury 62, 20, and 2 days after starting ITZ-administration, respectively (Table 1), which is consistent with the previous report that the time period to exhibit elevations in LFTs after starting ITZ administration varied from several days to several weeks in ITZ-induced liver injury (Lavrijsen et al, 1992;Hann et al, 1993;Gallardo-Quesada et al, 1995;Srebrnik et al, 2005). In the present study, day 0 was defined as the day on which ITZ administration was started for patients 1 and 2.…”
Section: Abnormalities In Lftssupporting
confidence: 80%
“…ITZ has been reported to cause cholestatic liver injuries (Lavrijsen et al, 1992;Hann et al, 1993;Gallardo-Quesada et al, 1995;Srebrnik et al, 2005), and our clinical data also suggested a cholestatic effect of ITZ with elevations of ALP, ␥-GTP, and direct bilirubin (Fig. 1).…”
Section: Abnormalities In Lftssupporting
confidence: 51%
See 2 more Smart Citations
“…Itraconazole pulse therapy was safe, at present there were only two reports of life-threatening hepatitis after itraconazole pulse therapy. 22,23 In our study, one patient (4.5%) developed slight facial oedema and none experienced severe side effects or laboratory abnormalities. But there were no significant differences between the rates of side effects of the two groups.…”
Section: Discussionmentioning
confidence: 90%